2009
DOI: 10.1136/jmg.2009.067637
|View full text |Cite
|
Sign up to set email alerts
|

Microdeletions including YWHAE in the Miller-Dieker syndrome region on chromosome 17p13.3 result in facial dysmorphisms, growth restriction, and cognitive impairment

Abstract: Microdeletions of chromosome 17p13.3 involving YWHAE present with growth restriction, craniofacial dysmorphisms, structural abnormalities of brain and cognitive impairment. The interstitial deletions are mediated by diverse molecular mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
37
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(44 citation statements)
references
References 33 publications
7
37
0
Order By: Relevance
“…We describe a recognisable but variable phenotype in eight individuals with microdeletions (table 5 and figure 3a) in 17p13.3 consistent with that recently described by Sreenath Nagamani et al 15 All individuals with 17p13.3 microdeletions had developmental delay of varying degree, except the patient in case 5, who had only mild learning difficulties, and the mother (6c) in cases 6a and 6b who, however, experienced transient speech problems as a young child. None displayed behavioural problems.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…We describe a recognisable but variable phenotype in eight individuals with microdeletions (table 5 and figure 3a) in 17p13.3 consistent with that recently described by Sreenath Nagamani et al 15 All individuals with 17p13.3 microdeletions had developmental delay of varying degree, except the patient in case 5, who had only mild learning difficulties, and the mother (6c) in cases 6a and 6b who, however, experienced transient speech problems as a young child. None displayed behavioural problems.…”
Section: Discussionsupporting
confidence: 87%
“…Owing to its function in the central nervous system,12 22 YWHAE is very likely to play a role in the phenotypes of the deletion patients. CRK is the likely candidate for growth restriction; notably, case 1 described by Sreenath Nagamani et al 15 and the single case described by Mignon-Ravix et al 13 showed neither growth restriction nor deletion of CRK (figure 1a and tables 2, 3 and 5). Benign CNVs within the deletion minimal overlapping region (MRO) have not been reported in a series of 891 healthy individuals (see Methods) nor in the Database of Genomic Variants (http://projects.tcag.ca/variation/) or the CHOP CNV Database (http://cnv.chop.edu/).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Changes in 14-3-3ϵ dosage have been shown to alter neuronal migration, thereby impairing proper neurodevelopment [27]. Several studies have previously indicated that large duplications or deletions at 17p13.3 affecting this gene are associated with developmental delay or autism [20,28-30]. The small 24-kb duplication that we identified in our study has also been noted in our past work [31] and in clinical cohorts.…”
Section: Discussionsupporting
confidence: 84%